Predyktory upadłości spółek z o.o. oraz spółek akcyjnych - Korol, Tomasz (Bankruptcy Predictors for Limited Liabilities and Stock Companies, 2007)
This article is on prediction of the bankruptcy of stock equity companies and limited liabilities firms in Poland. The author concentrates on finding the best financial ratios - predictors of bankruptcy for these two different types of companies. In the research the artificial intelligence has been used to predict the financial crisis of the companies. Presented models in the article distinguish with high effectiveness of predicting the bankruptcy among accessible results in the literature in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 313-321